Spatial networks, labor supply, and income dynamics: Evidence from Indonesian villages - Yamauchi, Futoshi; Muto, Megumi; Chowdhury, Shyamal; Dewina, Reno; Sumaryanto, Sony (International Food Policy Research Institute, 2009)
This paper uses household panel and village census data from Indonesia to examine the impact of spatial connectivity (road) development on household income growth and nonagricultural labor supply. The empirical results show that the impacts of improvements in local road quality (which positively correlate with transportation speed) on income growth and the transition to nonagricultural labor markets depend on the distance to economic centers and the household education level. In particular, postprimary education significantly increases the benefit from local spatial connectivity improvement in remote areas and promotes labor transition to nonagricultural sectors. Education and local road quality are complementary, mutually increasing income growth and nonagricultural labor income in remote areas. The gain from improvements in local connectivity (measured by average road quality) depends on village remoteness and initial household-level endowments.